Temperature responsive smart polymer for enabling affinity enrichment of current coronavirus (SARS-CoV-2) to improve its diagnostic sensitivity - Nabil, Ahmed (Comput Struct Biotechnol J, 2021)
The current commercially available SARS-CoV-2 diagnostic approaches including nucleic acid molecular assaying using polymerase chain reaction (PCR) have many limitations and drawbacks. SARS-CoV-2 diagnostic strategies were reported to have a high false-negative rate and low sensitivity due to low viral antibodies or antigenic load in the specimens, that is why even PCR test is recommended to be repeated to overcome this problem. Thus, in anticipation of COVID-19 current wave and the upcoming waves, we should have an accurate and rapid diagnostic tool to control this pandemic. In this study, we developed a novel preanalytical strategy to be used for SARS-CoV-2 specimen enrichment to avoid misdiagnosis. This method depends on the immuno-affinity trapping of the viral target followed by in situ thermal precipitation and enrichment. We designed, synthesized, and characterized a thermal-responsive polymer poly (N-isopropylacrylamide-co-2-hydroxyisopropylacrylamide-co-strained alkyne isopropylacrylamide) followed by decoration with SARS-CoV-2 antibody. Different investigations approved the successful synthesis of the polymeric antibody conjugate. This conjugate was shown to enrich recombinant SARS-CoV-2 nucleocapsid protein samples to about 6 folds. This developed system succeeded in avoiding the misdiagnosis of low viral load specimens using the lateral flow immunoassay test. The strength of this work is that, to the best of our knowledge, this report may be the first to functionalize SARS-CoV-2 antibody to a thermo-responsive polymer for increasing its screening sensitivity during the current pandemic.